Rural entrepreneurship: An analysis of current and emerging issues from the sustainable livelihood framework - Alexander Tabares; Abraham Londo\~no-Pineda; Jose Alejandro Cano; Rodrigo Gómez-Montoya (Economies, 2022)
Most entrepreneurship studies have an urban focus, and it is studied mainly from the perspective of opportunity exploitation. Rural entrepreneurship presents different characteristics, and it requires analysis from a resource-based view since this kind of entrepreneurial behavior takes place in rural communities under resource constraints. The sustainable livelihood perspective represents a relevant framework in rural entrepreneurship, considering resources and capacities to face poverty in rural areas. Therefore, this study presents a literature review to identify current and emerging issues in rural entrepreneurship from a sustainable livelihood framework. The literature review identifies that the main concepts involved in rural entrepreneurship and sustainable livelihood are women, poverty alleviation, youth, social entrepreneurship, and institutions. Likewise, social capital and human capital prevail as the most relevant capitals in the analyzed documents. The study offers research opportunities in emerging issues related to social entrepreneurship, governance and institutions, livelihood growth, and eco-entrepreneurship for extending the boundaries of rural entrepreneurship from the sustainable livelihood framework.
Keywords: 330; poverty alleviation; rural entrepreneurship; social capital; social entrepreneurship; sustainable livelihoods; women; youth